2022
DOI: 10.1371/journal.pone.0263036
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming improved salt-stressed sorghum growth by enhancing antioxidative defense

Abstract: Seed priming is regarded as a beneficial and effective method enhancing performance of plants grown under stress conditions. This study illustrated the effect of four seed priming agents (2% H2O2, 52 mM NaCl, 50 mM KCl, 250 mM MgSO4) on two sorghum cultivars (Canada sorghum CFSH-30 and sorghum ‘1230’) grown in saline soils. Sorghum growth characteristics and biochemical parameters were investigated. Seed priming treatments alleviated the adverse effects of salt stress by decreasing MDA content and enhancing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The latter remained higher than control, even after stress had been discontinued, while the former returned to the untreated control level. These results were also recorded for sorghum [56,68], melon [69] and wheat [57], confirming the retention of high levels of osmoprotectants as a mechanism and explaining the role of salt priming in the enhancement of the subsequent tolerance to salt stress [67]. The importance of proline for osmotic adjustment in primed plants over TSS was confirmed in the present study by the higher level of proline in P/ShK plants, compared with Shk plants, while TSS were comparable in both plant groups.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The latter remained higher than control, even after stress had been discontinued, while the former returned to the untreated control level. These results were also recorded for sorghum [56,68], melon [69] and wheat [57], confirming the retention of high levels of osmoprotectants as a mechanism and explaining the role of salt priming in the enhancement of the subsequent tolerance to salt stress [67]. The importance of proline for osmotic adjustment in primed plants over TSS was confirmed in the present study by the higher level of proline in P/ShK plants, compared with Shk plants, while TSS were comparable in both plant groups.…”
Section: Discussionsupporting
confidence: 67%
“…Working on sweet sorghum, Yan et al [56] documented enhanced activity for SOD and APX in primed plants exposed to salt stress, compared with unprimed stressed conditions, while CAT appeared to be insignificantly affected with pretreatment. Working with the same species, Guo et al [68] found, surprisingly, that seed priming with NaCl was accompanied by higher levels of CAT and POX under salt stress, compared with the exposure to salt stress without priming. The same results were recorded for melon plants derived from saltprimed seeds [69].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in growth characteristics was more pronounced at a soil salinity of 8 dS m −1 . Previous studies, such as those by Guo et al (2022) and Dehnavi et al (2022), have shown that soil salinity negatively affects sorghum's fresh and dry weights. Plant growth regulators positively affect salinity tolerance by maintaining cell turgor and protecting plants from oxidative stress, thus increasing plant growth (Ibrahim, 2016; Mansour et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, by stimulating the plant antioxidant defense system in advance, it is possible to create a stress memory and increase stress tolerance (Sher et al, 2019). The effects of priming agents differ depending on their concentrations and the species of plant (Guo et al, 2022). Osmo-priming provides initiation of metabolic preparations for germination by controlling the water absorption in the seed under drought stress induced by polyethylene glycol (PEG) (Jisha et al, 2013;Abid et al, 2018).…”
Section: Kuraklık Stresi Altında Farklı Priming Uygulamalarının Buğda...mentioning
confidence: 99%